Langerin+CD8+ Dendritic Cells in the Splenic Marginal Zone: Not So Marginal After All - Backer, Ronald A.; Diener, Nathalie; Clausen, Björn E. (Frontiers in Immunology, 2019)
Dendritic cells (DC) fulfill an essential sentinel function within the immune system, acting at the interface of innate and adaptive immunity. The DC family, both in mouse and man, shows high functional heterogeneity in order to orchestrate immune responses towards the immense variety of pathogens and other immunological threats. In this review, we focus on the Langerin+CD8+ DC subpopulation in the spleen. Langerin+CD8+ DC exhibit a high ability to take up apoptotic / dying cells, and therefore they are essential to prime and shape CD8+ T cell responses. Next to the induction of immunity towards blood-borne pathogens, i.e. viruses, these DC are important for the regulation of tolerance towards cell-associated self-antigens. The ontogeny and differentiation pathways of CD8+CD103+ DC should be further explored to better understand the immunological role of these cells as a prerequisite of their therapeutic application.